Isolation and characterization of bacteriophages for controlling Rhizobium radiobacter – causing stem and crown gall of highbush blueberry - Chantapakul, Bowornnan; Sabaratnam, Siva; Wang, Siyun (Frontiers in Microbiology, 2024)
Introduction Stem and crown gall disease caused by the plant pathogen Rhizobium radiobacter has a significant impact on highbush blueberry (Vaccinium corymbosum) production. Current methods for controlling the bacterium are limited. Lytic phages, which can specifically target host bacteria, have been widely gained interest in agriculture. Methods In this study, 76 bacteriophages were recovered from sewage influent and screened for their inhibitory effect against Rhizobium spp. The phages were genetically characterized through whole-genome sequencing, and their lytic cycle was confirmed. Results Five potential candidate phages (isolates IC12, IG49, AN01, LG08, and LG11) with the ability to lyse a broad range of hosts were chosen and assessed for their morphology, environmental stability, latent period, and burst size. The morphology of these selected phages revealed a long contractile tail under transmission electron microscopy. Single-step growth curves displayed that these phages had a latent period of 80–110 min and a burst size ranging from 8 to 33 phages per infected cell. None of these phages contained any antimicrobial resistance or virulence genes in their genomes. Subsequently, a combination of two-, three- and four-phage cocktails were formulated and tested for their efficacy in a broth system. A three-phage cocktail composed of the isolates IC12, IG49 and LG08 showed promising results in controlling a large number of R. radiobacter strains in vitro. In a soil/peat-based model, the three-phage cocktail was tested against R. radiobacter PL17, resulting in a significant reduction (p < 0.05) of 2.9 and 1.3 log10 CFU/g after 24 and 48 h of incubation, respectively. Discussion These findings suggest that the three-phage cocktail (IC12, IG49 and LG08) has the potential to serve as a proactive antimicrobial solution for controlling R. radiobacter on blueberry.